Principles of two-dimensional design - Wong, Wucius (John Wiley & Sons, 1972)
Understanding the elements of two-dimensional design and the infinite options available in organizing choices made are at the core of this book. Wong surveys all concepts of forms and structures, covering most situations in two-dimensional composition, formal or informal.